Clearing the clouds: Case‐report and review of the literature. Issue 1 (2nd November 2020) - Relvas, Miguel; Beco, Ana; Pereira, Luciano; Oliveira, Ana; Silvano, José; Silva, Rui; Marques, Nídia; Santos, Lurdes; Coentrão, Luís; Pestana, Manuel
Abstract: In peritoneal dialysis (PD), a cloudy dialysate is an alarming finding. Bacterial peritonitis is the most common cause, however, atypical infections and non‐infectious causes must be considered. A 46‐year‐old man presented with asthenia, paraesthesia, foamy urine and hypertension. Laboratory testing revealed severe azotaemia, anaemia, hyperkalaemia and nephrotic‐range proteinuria. Haemodialysis was started through a central venous catheter. Later, due to patient preference, a Tenckhoff catheter was inserted. Conversion to PD occurred 3 weeks later, during hospitalization for a presumed central line infection. A month later, the patient was hospitalized for neutropenic fever. He was diagnosed an acute parvovirus infection and was discharged under isoniazid for latent tuberculosis. Four months later, the patient presented with fever and a cloudy effluent. Peritoneal fluid (PF) cytology was suggestive of infectious peritonitis, but the symptoms persisted despite antibiotic therapy. Bacterial and mycological cultures were negative. No neoplastic cells were detected. Mycobacterium tuberculosis eventually grew in PF cultures, despite previous negative molecular tests. Directed therapy was then initiated with excellent response. Thus, facing a cloudy effluent, one must consider multiple aetiologies. Diagnosis of peritoneal tuberculosis is hampered by the lack of highly sensitive and specific exams. Here, diagnosis was only possible due to positive mycobacterial cultures.